2011
DOI: 10.1021/cg200277a
|View full text |Cite
|
Sign up to set email alerts
|

Probing Intermolecular Crystal Packing in γ-Indomethacin by High-Resolution 1H Solid-State NMR Spectroscopy

Abstract: An NMR crystallography approach that combines experimental solid-state magic-angle-spinning (MAS) NMR with calculation is applied to the  polymorph of the pharmaceutical molecule, indomethacin. First-principles calculations (GIPAW) for the full crystal structure and an isolated molecule show changes in the 1 H chemical shift for specific aliphatic and aromatic protons of over 1 ppm that are due to intermolecular CH- interactions. For the OH proton, 1 H double-quantum (DQ) CRAMPS (combined rotation and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 62 publications
4
53
0
Order By: Relevance
“…Overall, the agreement between the 14 calculated and experimental values in Figure is relatively good, given the narrow 1 H chemical shift range and the imprecision of the 1 H δ iso measurements taken using the 2D CP–HETCOR spectrum. The agreement seen in Figure is similar to or better than the agreement between 1 H δ iso and σ iso (the latter calculated using GIPAW calculations) observed in other systems . It is known that improved agreement is possible if a series of variable‐temperature studies are performed and the experimental δ iso measurements obtained are used to extrapolate theoretical δ iso values at 0 K .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, the agreement between the 14 calculated and experimental values in Figure is relatively good, given the narrow 1 H chemical shift range and the imprecision of the 1 H δ iso measurements taken using the 2D CP–HETCOR spectrum. The agreement seen in Figure is similar to or better than the agreement between 1 H δ iso and σ iso (the latter calculated using GIPAW calculations) observed in other systems . It is known that improved agreement is possible if a series of variable‐temperature studies are performed and the experimental δ iso measurements obtained are used to extrapolate theoretical δ iso values at 0 K .…”
Section: Resultssupporting
confidence: 78%
“…The agreement seen in Figure 8 is similar to or better than the agreement between 1 H * iso and F iso (the latter calculated using GIPAW calculations) observed in other systems. [49][50][51] It is known that improved agreement is possible if a series of variable-temperature studies are performed and the experimental * iso measurements obtained are used to extrapolate theoretical * iso values at 0 K. 49 This approach was not necessary with Form 1 given the clear assignments of the 14 observed 1 H positions.…”
Section: H and 13 C Ssnmr Analysismentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Recent studies by Surwase et al reported new crystalline forms of IMC and water driven phase transitions from an amorphous phase, in spite of years of studies. 23 The thermodynamically most stable form of indomethacin (g-IMC) has the space group symmetry P% 1 with Z 0 = 1.…”
Section: Resultsmentioning
confidence: 99%
“…Conversions to other chemical shift scales can be accomplished as described by Ref 37; for expediency, several of the most common conversions are given in the ESI. † The CSD reference codes and experimental references for NMR data for the three test sets are: Hydrogen (13 structures, 80 shifts): CIMETD, 1 INDMET, 38 URACIL, 39 co-crystal of 4,5-Dimethylimidazole and 3,5-Dimethylpyrazole, 40 AMBACO05, 41 PHBARB06, 42 IPMEPL, 7 COYRUD11, 43 FPAMCA11, 8 BAPLOT01, 8 WEZCOT, 8 FLUBIP, 44 ZIVKAQ. 45 …”
Section: Methodsmentioning
confidence: 99%